High-aluminum orthopyroxene megacrysts (HAOM) in the Ahvenisto complex, SE Finland, and the polybaric crystallization of massif-type anorthosites - Heinonen, Aku; Kivisaari, Heli; Michallik, Radoslaw (Contributions to Mineralogy and Petrology, 2019)
The occurrence of high-aluminum orthopyroxene megacrysts (HAOMs) in several massif-type Proterozoic anorthosite complexes has been used as evidence of their polybaric crystallization. Here, we report such petrographic and geochemical (XRF and EMPA) evidence from HAOMs discovered in the 1.64 Ga Ahvenisto rapakivi granite-massif-type anorthosite complex in southeastern Finland. Two different types of HAOMs were recognized: type 1 HAOMs are individual, euhedral-to-subhedral crystals, and up to 15 cm in diameter, and type 2 HAOMs occur in pegmatitic pockets closely associated with megacrystic (up to 30 cm long) plagioclase. The type 1 megacrysts in particular are surrounded by complex corona structures composed of plagioclase, low-Al orthopyroxene, iddingsite (after olivine), and sulfides. Orthopyroxene crystallization pressure estimates based on an Al-in-Opx geobarometer reveal a three-stage compositional evolution in both textural HAOM types. The Al content decreases significantly from the core regions of the HAOM (4.4-7.6 wt% Al2O3), through the rims (1.3-3.6 wt%), into the host rock (0.5-1.5 wt%). Enstatite compositions overlap, but are generally higher in the cores (En(similar to 60-70)) and rims (En(similar to 50-70)) of the HAOMs than in the host rock (En(similar to 45-60)) orthopyroxenes. The highest recorded Al abundances in the HAOM cores correspond to crystallization pressures of up to similar to 1.1 GPa (similar to 34 km depth), whereas the HAOM rims have crystallized at lower pressures (max. similar to 0.5 GPa, 20 km depth). The highest pressure estimates for the host rock orthopyroxene were similar to 0.2 GPa (<7 km depth). These observations confirm the polybaric magmatic evolution of the Ahvenisto anorthosites and suggest that the entire 1.65-1.55 Ga Fennoscandian rapakivi suite was emplaced at a relatively shallow level (<7 km depth) in the upper crust. Global comparison to similar rock types reveals remarkable similarities in the petrogenetic processes controlling HAOM composition and ...